Will global warming reduce the nutritional quality of wild blueberries? - Oluwafemi A Alaba; Sofiane Bechami; Yu-Ying Chen; Tawanda W Gara; Brian Perkins; Yong-Jiang Zhang (Climate Change Ecology)
Anthropogenic climate change may affect the nutritional quality of perennial crops. Wild blueberry is a perennial crop of cultural and economic importance and known for its health-promoting properties. Wild blueberry fields in Maine, USA are experiencing unprecedented warming, which may affect the quality and marketability of the fruit. We examined the biochemistry of wild blueberries grown under active open-top heating that elevated temperatures by 3.3 °C, passive open-top heating by 1.2 °C, and ambient conditions (control). We found that total soluble solids, fructose, total soluble sugars and total soluble protein decreased as temperatures increased. In contrast, anthocyanin, total flavonoid and phenolics were not affected. Additionally, warming weakened the correlation between sugars, total soluble solids, and other components. Our results suggest that future global warming may reduce the nutritional value and marketability of wild blueberries. Potential mitigation techniques will need to be developed for future production.